Terrorism as Impediments To Democracy In Nigeria - Tella, Charas Madu; Bello, Umar Mohammed; Adejeumo, Abdulhakeem (Advances in Social Sciences Research Journal, 2018)
Terrorism has been conceptualized as an act of violent conflict, armed conflict, insurgency, bombing, kidnapping, assassination, sabotage and a series destructive activities leading to the use of physical force against another person or group aimed at either causing death, temporal or perpetual injury or drawing government's, groups' or individual attention for relevance and recognition. The word terrorism did not, however, feature more prominently in the minds of people until after the US 9/11 World Trade Center bombings. These acts were not only to create panic, fear and anxiety but also to undermine security and political leadership of the country targeted. Since the September 11th, terrorism has continued to spread and have taken a new dimension across the globe and Nigeria was, thus, not an exception. The objective of this research is to examine the effects of terrorism and violence on development of democracy in Nigeria. The research employed primary and secondary data. 300 questionnaires were distributed, retrieved and analyzed using chi-square techniques. The findings revealed among other things that terrorism has consequent effects on the development of democracy in Nigeria. Finally, the research recommended that elections and its myriad of processes must be free, fair and transparent in addition to being devoid of violence and conflicts. The culture of stuffing ballot boxes with paper constitutes a serious challenge and the outcome in most situations contradict the choice of the electorate. Therefore, the electoral processes should be more fervently strengthened to avoid crises and their related consequences.